Plan estratégico y su relacion con el direccionamiento administrativo de la empresa “banco finca” cantón Quevedo, periodo 2014 - 2018 - Gorotiza Morán, Gladys Lourdes (2015)
The present research, it performs in order to design a strategic plan for business growth the Bank Finca Quevedo Canton, Period 2014-2018. . It is intended that in this research, the need for a strategic plan for the company to Bank Finca efficiently determine its objectives and strategies proposed in order to achieve greater competitiveness in the market, and similarly positioned therein, This plan will allow according to the scenarios presented to delineate operational executives to achieve their goals through efficiency and effectiveness as security against its customers by offering better performance in the various areas in which it operates strategies; These institutional objectives, policies, strategic guidelines will target the effectiveness of their action plans, and enjoining the respective strategic indicators show what has been done during the administrative process of the organization, This research presents a conceptual model with an idea or an image by generalizing particular, this operating model is to be used in the company. Keywords: research, strategic plan, company strategies.